Investigation on surface defect machining of AISI 4340 steel. (2022) - Jayakumar, N.; Senthilkumar, G.; Vignesh Kumar, S.
Abstract: Hardened steel turning is now an issue due to the needed less machining force and surface roughness. Due to it having medium carbon (0.4% C) it is high strength martensitic steel. AISI 4340 steel has been utilized for this experiment on surface defect machining (SDM). In demanding applications such as aerospace and automotive transmissions, this material is particularly significant. In order to machine ferrous alloy having a hardness of over 45 HRC, for removing the material cutting tool with single point operating at high speeds. A typical approach is used to process hard steel, and those procedures require a large amount of money and time. The need for annealing and grinding is eliminated when compared with surface defect machining. Researchers are keeping on looking for the ideal amalgamation of inserts in HT, where the life of the tool is important because of the expense and the desire for a superior surface finish. For finding the most ideal parameters for surface defect machining by considering input parameters such as feed rate, depth of cut, and cutting speed. Taguchi technique was utilized with an L9 orthogonal array and for ANOVA the Grey Relational Analysis (GRA) has been used. The results were obtained by performing Surface Defect Machining on hardened AISI 4340 steel. For this typical Surface Defect Machining, the Grey relation grade is used with the thought of machining force and Surface Roughness (SR) as the level of variables and the best combinations has found as 0.05 of feed mm/rev, 0.5 mm depth of cut and 900 rpm of cutting speed.